Growing bulk-like 3C-SiC from seeding material produced by CVD - Schuh, Philipp; Arzig, Matthias; Litrico, G.; La Via, F.; Mauceri, M.; Wellmann, Peter (physica status solidi (a), 2017)
We present a process to transfer CVD grown heteroepitaxial 3C-SiC on Si onto polycrystalline SiC, involving an etching step to get rid of the Si and a homogeneous carbon glue deposit, facilitating the resulting compound to be used as a seeding material for further growth process. In a sublimation sandwich setup, realized within an inductively heated physical vapor transport reactor, used for bulk growth of SiC, the thickness of the 3C-SiC seed was increased up to 850μm while keeping the cubic polytype. With the introduction of Ta as a carbon getter, the gas phase composition is optimized in order to achieve an improved growth front. Single crystalline growth is confirmed by Laue diffraction and Raman measurements. The Raman peaks are shifted to higher wavenumbers, indicating compressive stress in the grown samples. Furthermore, a scale up of the process is demonstrated, showing the feasibility of growing 3C-SiC on an area of 10.5cm in a 2inch setup featuring a thickness of approximately 570μ
Keywords: 3C-SiC; bulk crystals; layer transfer; physical vapor transport